Impact of specific serotonin receptor modulation on restricted repetitive behaviors - Alvarez, Bryan D.; Cavazos, Cassandra; Morales, Cheyenne A.; M. Lopez, Shannon; Amodeo, Dionisio A. (Frontiers in Behavioral Neuroscience, 2022)
Restricted, repetitive behaviors (RRBs) are commonly divided into two behavioral categories, lower order and higher order RRBs. Individuals displaying lower order motoric RRBs may express repetitive hand flapping behaviors, body rocking back and forth movements, and continuous body spinning. In rodents, lower order RRBs are commonly measured through various tasks, such as repetitive self-grooming, marble burying, and stereotypic motor behaviors. This review focuses on the effects that modulation of specific serotonin receptors have on lower order RRBs. Although there is research examining how changes in 5-HT1A, 5-HT1B, 5-HT2A, 5-HT2B, 5-HT2C, 5-HT3, 5-HT6, and 5-HT7 receptor modulation, more research has focused on the 5-HT1A, 5-HT2A and 5-HT2C receptors. The accumulating data suggest that increasing 5-HT1A activation decreases RRBs, while blocking 5-HT1A activation has no effect on RRBs. While there are mixed findings regarding the impact of 5-HT2A modulation on RRBs, the general trend shows mixed effects of 5-HT2A activation RRB expression, whereas blockades generally decreases RRBs. 5-HT2C receptor activation can modulate RRBs in either direction depending on the 5-HT2C drug used, blocking 5-HT2C activation only seems to show therapeutic properties when 5-HT2C activation is already elevated. The other 5-HT receptors have been explored far less, but show promise as potential targets for regulating RRBs. Increasing 5-HT3 has not been shown to affect RRBs. 5-HT6 activation can increase RRBs, and blocking 5-HT6 activity decreases RRBs. Lastly, either increasing or blocking 5-HT7 activity can reduce RRBs.